Investigation of Copy Number Variation in South African Patients with Congenital Heart Defects - Saacks, Nicole Aimee (Department of Paediatrics and Child Health, 2021)
Background: Congenital heart disease (CHD) is the leading non-infectious cause of paediatric morbidity and mortality worldwide and a significant social and healthcare burden. The aetiology of CHD is poorly understood, though heritable genetic factors including copy number variants (CNVs) have been shown to contribute to the risk of CHD in individuals of European ancestry. However, the role of rare CNVs in the development of CHD in African populations including South Africa is unknown. This study aims to identify pathogenic and likely pathogenic CNVs in South African cases of CHD. To our knowledge, this is the first study to investigate the genetic basis of CHD in a South African cohort. Methods: The study cohort included 105 patients presenting to the cardiac clinics at Red Cross War Memorial Children's Hospital and Groote Schuur Hospital with non-syndromic isolated CHD (n = 76), nonsyndromic CHD with additional extra-cardiac anomalies (n = 17), and positive controls with syndromic CHD (n = 12). Genotyping was performed using the Affymetrix CytoScan HD platform. Rare CNVs were filtered using stringent criteria for their size and algorithm-specific quality score and were compared against a gene panel of known CHD-associated genes. Candidate genes were considered based on pLI scores and reported CHD phenotypes in mouse models. The identified CNVs were validated by quantifying the read-coverage of available whole-exome sequencing data of a similar overlapping cohort. Results: Chromosomal microarray analysis was successful for 101 participants (including 89 non-syndromic CHD cases and 12 control cases) and led to the identification of eight CNVs overlapping genes known to be causal for CHD (GATA4, TBX1, FLT4, CRKL, NSD1, and B3GAT3), and four CNVs encompassing candidate genes likely to play a role in the development of CHD (DGCR8, JARID2, KDM2A, and FSTL1). The CNVs were identified in nine unrelated individuals: five of the CNVs were classified as pathogenic or likely pathogenic (5.6% of the cohort) and four were classified as variants of unknown significance (4.6%). CNVs of interest were validated using the available whole-exome sequencing data. Conclusions: In this study, we show that chromosomal microarray analysis is an effective technique for identifying CNVs in patients diagnosed with CHD and that this approach can be performed locally in South Africa, producing results similar to those seen in international CHD studies. The findings of this thesis highlight the wide genetic heterogeneity of CHD and the growing importance of CHD genetic studies for both research and clinical purposes. Advancing our understanding of CHD aetiology will help define disease risk in South Africa and improve the way we care for and assess our cardiac patients.